The Relationship Between Of Using A Learning Gadget With The Result From Student Learning Attitude In The Food Service Subject At Smk Negeri 6 Padang - Febria, Lisya; Yelfi, Reno (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research is motivated by the emergence of positive and negative impacts in the use of gadget learning media, in addition to the positive impact, the use of gadget learning media has a negative impact, namely making students more individual rather than socializing, even though it is expected that by using this gadget students can gain more knowledge from each other. exchange information with friends to create a fun learning attitude This study aims to this research is to describe the  of using gadget media, describing learning outcomes and analyzing whether there is a relationship between the impact of usinga learning gadget with the result from student learning in the food service . This type of research is a quantitative correlational approach. The results of the study are from the average variable score, the impact of using gadget learning media obtains a respondent achievement level (TCR) of 3.66 in the high category. From the average variable score, the learning outcomes obtained the respondent's achievement level (TCR) of 4.11 in the high category. There is a positive and significant relationship between the variable impact of the use of gadget learning media and the results of learning food service at SMKN 6 Padang, where the level of relationship between the two variables is in a fairly high category.